Um estudo quanto as práticas de governança corporativa adotadas pelas entidades fechadas de previdência complementar - Rocha Neto, Nilter Rodrigues da (Universidade Federal Rural do Semi-Árido, 2018)
The general objective of this article is to investigate the Corporate Governance practices disclosed by the Closed Entities of Complementary Pension Plans through its electronic websites, Annual Reports and in force Statutes. To achieve this objective, relevant aspects regarding information transparency were raised in accordance with legal and regulatory requirements. The research can be delineated as a statistical and quantitative induction of description. The sample is composed of 228 companies, where a questionnaire with dummy variables analysis was used. It is verified in the analysis of the collected data that the entities publish the basic information for the most parts, being the voluntary practices of heterogeneous form, where certain items reached high values of disclosure and others reached very low scores. On the other hand, the analysis of the data also included that companies, try to divulge only the data that are requested by norm or law. It was also verified the increase in the appearance of new sites in relation to the number of companies listed by the National Superintendency of Complementary Pensions, however, it was verified that there is a great need for improvements in the availability of information.
Artigo Acadêmico
Keywords: Governança corporativa; Divulgação; Fundos de pensão; Corporate governance; Disclosure; Pension funds; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::CIENCIAS CONTABEIS